Pharmacogenetic Variation in Over 100 Genes in Patients Receiving Acenocumarol - Gonzalez-Covarrubias, Vanessa; Urena-Carrion, Javier; Villegas-Torres, Beatriz; Cossío-Aranda, J. Eduardo; Trevethan-Cravioto, Sergio; Izaguirre-Avila, Raul; Fiscal-López, O. Javier; Soberon, Xavier (Frontiers in Pharmacology, 2017)
Coumarins are widely prescribed worldwide, and in Mexico acenocumarol is the most preferred form. It is well known that despite its efficacy, coumarins show a high variability for dose requirements. We investigated the pharmacogenetic variation in 110 genes in patients receiving acenocumarol using a targeted NGS approach. We report relevant population differentiation for variants on CYP2C8, CYP2C19, CYP4F11, CYP4F2, PROS, and GGCX, VKORC1, CYP2C18, NQO1. A higher proportion of novel-to-known variants for 10 genes was identified on 41 core pharmacogenomics genes related to the PK (29), PD of coumarins (3), and coagulation proteins (9) including, CYP1A1, CYP3A4, CYP3A5, and F8, and a low proportion of novel-to-known variants on CYP2E1, VKORC1, and SULT1A1/2. Using a Bayesian approach, we identified variants influencing acenocumarol dosing on, VKORC1 (2), SULT1A1 (1), and CYP2D8P (1) explaining 40 – 55% of dose variability. A collection of pharmacogenetic variation on 110 genes related to the PK/PD of coumarins is also presented. Our results offer an initial insight into the use of a targeted NGS approach in the pharmacogenomics of coumarins in Mexican Mestizos.